Factors of Participants and Blogs that Predict Blogging Activeness During Teaching Practice and Induction Year - Luik, Piret; Taimalu, Merle (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
The blog as a type of social software has been used in education for several years, and its positive effect in the field has been asserted in many studies. This study presents the factors of participants and blogs that predict blogging activeness during teaching practice and induction year. During the teaching practice and induction year all participants could use a blog to share experiences, ask questions, receive support, and so on. The blogs were supported by the tutors and all blogs were collective blogs, but they were organised differently and used differently. The data collected included 1,137 blog posts from 192 participants using 13 collective blogs along with their self-reports via pre- and post-period questionnaires. Multiple regression analysis was used in this study. The results showed that the most influential positive factors predicting participant activeness on the blog were the strength of social relationships between the participants and the pleasant and supportive atmosphere in the blog so that learners can feel blogging is suitable.